EMOTION REGULATION: PREDICTING SMART-SHAMING TENDENCY ON SOCIAL MEDIA COMMUNICATION - Mary Chris A. Austria; Irene M. Diaz, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
Smart-shaming has been nurtured by the false notion that “my ignorance is just as good as a discrete social phenomenon and required an aspect of self-regulation. The initial purpose of this study was explanatory and designed to measure whether smart-shaming is an emotional response and an endpoint of cognitive inconsistency. This notion was best explained in the light of Festinger (1957) theory of Cognitive Dissonance. This study examined the causes, motivations and behaviours of individuals on social media. The underlying forces as to how people process their cognitive functions of reappraisal and expression suppression is the focal point of this study. This paper was divided into two parts. A total of 406 respondents with the age range of 18-43 years old with social networking programs participated in this study. In study 1, there were two hundred fifty-six (256) participants answered Emotion Regulation Questionnaire (ERQ) and Online Smart Shaming Scale (OSS). In study 2, there were sixty (60) selected participants out of one hundred fifty (150) social media users. This part used nine (9) vignette stories that were based from the Online Smart Shaming Scale. In study 1, researchers’ used correlational design for data gathering procedure and linear regression for data analysis and found that a low level of emotion regulation promotes smart-shaming tendency. Specifically, low cognitive reappraisal and expression suppression promotes smart-shaming tendency. In study 2, T-test was utilized to determine the difference of high and low Cognitive Reappraisal and Expression Suppression scores for Smartshaming tendency. In study 2, T-test was utilized to determine the difference of high and low Cognitive Reappraisal and Expression Suppression study to reveal that there is a significant difference (p>0.05) between the two scores. In relation with the initial hypothesis, there is a negative relationship between emotion regulation and smart-shaming tendency. Likewise, cognitive processing and emotion regulation are intertwined constructs.